Analisis Konten Youtube sebagai Jaminan Fidusia pada Perbankan Syariah - Sutikno, Annisyatulhuda Rani Ayuningtyas; Sabiq, Fairuz; Nashirudin, Muh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
After the promulgation of Government Regulation Number 24 of 2022, copyright should be a breath of fresh air. However, the response given by financial institutions was only supportive and they did not have the courage to implement YouTube content as collateral. The method used in this research is the juridical-normative research method. The approach used in this research is the statutory approach. The data analysis technique used is the theory of Miles and Huberman, where there is data reduction, data presentation and conclusion. The government facilitates calculation assistance for intellectual property, but there are still many gaps in the application of these regulations. So we need a system or standard rules that regulate explicitly how to evaluate intellectual property economically. There are still many shortcomings in implementing Youtube content as a fiduciary guarantee, so additional regulations and a qualified system are still needed if you want to apply copyright as a fiduciary guarantee. Keywords : collateral, fiduciary, youtube.